Impact of acute exposure to WTC dust on ciliated and goblet cells in lungs of rats. (June 2015) - Cohen, Mitchell D.; Vaughan, Joshua M.; Garrett, Brittany; Prophete, Colette; Horton, Lori; Sisco, Maureen; Ghio, Andrew; Zelikoff, Judith; Lung-chi, Chen
Abstract Clinical studies and the World Trade Center (WTC) Health Registry have revealed increases in the incidence of chronic (non-cancer) lung disorders among first responders (FR) who were at Ground Zero during the initial 72 h after the collapse. Our previous analyses of rats exposed to building-derived WTC dusts using exposure scenarios/levels that mimicked FR mouth-breathing showed that a single WTC dust exposure led to changes in expression of genes whose products could be involved in the lung ailments, but few other significant pathologies. We concluded that rather than acting as direct inducers of many of the FR health effects, it was more likely inhaled WTC dusts instead may have impacted on toxicities induced by other rescue-related co-pollutants present in Ground Zero air. To allow for such effects to occur, we hypothesized that the alkaline WTC dusts induced damage to the normal ability of the lungs to clear inhaled particles. To validate this, rats were exposed on two consecutive days (2 h/d, by intratracheal inhalation) to WTC dust (collected 12–13 September 2001) and examined over a 1-yr period thereafter for changes in the presence of ciliated cells in the airways and hyperplastic goblet cells in the lungs. WTC dust levels in the lungs were assessed in parallel to verify that any changes in levels of these cells corresponded with decreases in host ability to clear the particles themselves. Image analyses of the rat lungs revealed a significant decrease in ciliated cells and increase in hyperplastic goblet cells due to the single series of WTC dust exposures. The study also showed there was only a nominal non-significant decrease (6–11%) in WTC dust burden over a 1-yr period after the final exposure. These results provide support for our current hypothesis that exposure to WTC dusts caused changes in airway morphology/cell composition; such changes could, in turn, have led to potential alterations in the clearance/toxicities of other pollutants inhaled at Ground Zero in the critical initial 72-h period.